Sodium glucose transporter 2 (SGLT2) inhibition and ketogenesis - Sanjay Kalra; Rakesh Sahay; Yashdeep Gupta (Indian Journal of Endocrinology and Metabolism, 2015)
Sodium glucose transporter 2 (SGLT2) inhibitors are a recently developed class of drug that have been approved for use in type 2 diabetes. Their unique extra-pancreatic glucuretic mode of action has encouraged their usage in type 1 diabetes as well. At the same time, reports of pseudo ketoacidosis and ketoacidosis related to their use have been published. No clear mechanism for this phenomenon has been demonstrated so far. This communication delves into the biochemical effects of SGLT2 inhibition, discusses the utility of these drugs and proposes steps to maximize safe usage of the molecules.